Transforming Conventional Teaching Classroom to Learner-Centred Teaching Classroom Using Multimedia-mediated Learning Module - Yap, Wei Li (2016)
There are higher education institutions in Malaysia which at the stage of transforming from teacher-centred teaching in the classroom to a more learner-centred teaching environment. The process has been slow due to lack of guidelines provided and teachers are lack of confidence. This research addresses the difficulties or challenges faced by the higher education institutions in such effort and also further investigate the impact of learner-centred teaching. A case study was conducted at INTI International University, Malaysia where it realized the limitations of conventional teaching and had taken initiatives to encourage lecturers to adopt a more learner-centred teaching approach. This research was found to be significant because there are many discussions which focused on various learning activities for student-centred learning but there is lack of focus given on the teachers, what teachers can do in order to achieve student-centred learning, especially for education institutions which are at the beginning stage of moving towards student-centred learning environment. With the assistance of technology, various learning tools or techniques were introduced and incorporated into teaching and learning process. This includes the online learning environment which supports synchronous and asynchronous learning. Besides that, multimedia technology can also be used in designing the learning module as it can gain better attention from students, increase learner motivation and improve retention rate. This research adopted Weimer’s Learner-Centred Teaching model which addresses key strategies to help education institutions to achieve such transformation in a more systematic approach by having clear guidelines for teachers. This study compared the conventional teaching with the multimedia learning and also the online learning in terms of their implications on learner understanding and learner motivation through the use of pre-test/ post-test, surveys and students’ comments.